Case report: Tension pneumoperitoneum after diagnostic colonoscopy in an 11 y/o boy with Crohns disease - Seitz, Sigurd; Rückel, Aline; Siebenlist, Gregor; Besendörfer, Manuel; Schellerer, Vera (International Journal of Surgery Case Reports, 2020)
Introduction: Endoscopy is an established diagnostic and therapeutic tool in paediatric gastroenterology and a save method with rare complications. Presentation of case: We present the case of an 11-year-old Caucasian boy with a long history of inflammatory bowel disease. Three years prior an ileostomy was created and is still in position. After diagnostic panendoscopy (colonoscopy, gastroscopy, endoscopy of small intestine via ileostomy) the patient showed progressive abdominal distension and pain. After diagnosis of tension pneumoperitoneum by radiological proof of massive intraabdominal air and altered vital signs, we initiated emergency laparotomy. Surgical intervention ruled out a free gastrointestinal perforation as well as peritonitis. There was a gaseous insufflation of the mesenteric tissue of the sigmoid and upper rectum most likely according to microperforations to the mesentery. Due to the pre-existing ileostomy, we took no further surgical action. The abdomen was lavaged and drains inserted. Upon further conservative treatment with intravenous antibiotics, the patient showed quick recovery and was discharged on postoperative day 6. Discussion: With an incidence of 0.01%, perforation after diagnostic colonoscopy in children is very uncommon. The zone most frequently affected is the sigmoid colon due to direct penetration or indirect force due to flexure, or insufflation. Even without macroscopic perforation, the development of a tension pneumoperitoneum seems to be possible. Conclusion: Even though Colonoscopy in children is a safe tool, the treating physician must never underestimate the risks of such an intervention. Especially chronically altered intestine as in long-time persisting chronic inflammatory bowel disease demand special care and intensive observation of the patient after intervention.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Child; Colonoscopy; Crohns disease; Pneumoperitoneum

Increased Incidence of Perforated Appendicitis in Children During COVID-19 Pandemic in a Bavarian Multi-Center Study - Schafer, Frank-Mattias; Meyer, Johannes; Kellnar, Stephan; Warmbrunn, Jakob; Schuster, Tobias; Simon, Stefanie; Meyer, Thomas; Platzer, Julia; Hubertus, Jochen; Seitz, Sigurd; Knorr, Christian; Stehr, Maximilian (Frontiers in Pediatrics, 2021)
Introduction: Since early 2020 the COVID-19 pandemic and statutory preventive reorganization of treatment capacities with cancellation of elective surgery as well as curfew regulations led to vastly decreased utilization of primary health care.
CRIS-Team WoS Importer:2021-05-28